Pengaruh Kesejahteraan Kerja Dan Job Well-Being Terhadap Retensi Melalui Employee Engagement - Widiawati Ai Hayati (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2026)
This study aims to examine the effect of work welfare and job well-being on employee retention, with employee engagement as a mediating variable among manufacturing company employees in Karawang Regency. A quantitative research approach with a survey method was employed. Primary data were collected through structured questionnaires distributed to permanent employees who had at least one year of work experience. Data analysis was conducted using Structural Equation Modeling (SEM) with the Partial Least Square (PLS) approach. The results indicate that work welfare and job well-being have a positive and significant effect on employee engagement and employee retention. Furthermore, employee engagement has a positive and significant effect on employee retention and acts as a partial mediator in the relationship between work welfare, job well-being, and employee retention. These findings highlight the importance of providing adequate work welfare and fostering positive psychological conditions at work to enhance employee engagement and encourage long-term retention. This study contributes to the human resource management literature and provides practical implications for manufacturing companies in developing sustainable human resource policies focused on employee well-being and engagement.